(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the current research is to determine the direct effect of trust in the tax administration on tax compliance, as well as the direct effect of the power of the tax administration, both legitimate and coercive, on tax compliance, and finally studying the interactive effect of trust and power in tax compliance for real profits income taxpayers in Lattakia Governorate, and to achieve the objectives of the research, The researcher used the questionnaire as a measurement tool, and distributed it to a random sample of real profits income taxpayers in Lattakia governorate, where the sample size amounted to 340 taxpayers from the community of 3000 taxpayers, during the year 2021. The results of the research concluded that there is a direct statistically significant effect for each trust and the legitimate power in tax compliance, and a statistically significant inverse effect of coercive power in tax compliance, and it was also found that there is a direct effect of the interactive case between trust and legitimate force in tax compliance, and an opposite effect of the interactive case between trust and coercive power in tax compliance. These results supported the assumptions of the slippery slope framework and emphasized the role of trust and power as important determinants of tax compliance, and the modifying role of both coercive and legitimate power in the relationship between trust in tax administration and tax compliance.